The Impact of Third-party Payments on Chinese Commercial Bank Profitability - xu, jiahui (2018)
In recent years, China's Internet finance has developed rapidly, especially the third-party payment, which has experienced explosive growth in transaction size. The emergence and development of third-party payment platforms not only prompted Chinese commercial banks to carry out financial innovation but also made commercial banks face the challenge of customer loss and deposit loss. At the same time, third-party payment companies use the network platform to provide professional financial services such as professional loans and wealth management to more and more financial consumers and may also affect the profits of commercial banks. At present, the research literature on the relationship between commercial banks and third-party payment is scarce, especially in empirical research. Therefore, this paper mainly discusses the direction and extent of influence of third-party payment on Chinese commercial banks. This paper examines the bank performance of 67 commercial banks in China from 2011 to 2016, using the dynamic panel data model to study the impact of third-party payments on the profits of Chinese state-owned commercial banks, Chinese joint-stock commercial banks and Chinese city commercial banks.The empirical results show that the impact of third-party mobile payment on China's city commercial banks and joint-stock commercial banks is positive, but not significant. However, third-party Internet payments have been found to have a significant negative impact on China's joint-stock commercial banks and city commercial banks. Because the number of Chinese state-owned commercial banks used in this paper is too small, resulting in insufficient empirical samples, most of China's state-owned commercial banks are supported by the Chinese government, and their status is difficult to shake, this paper does not summarize the impact of third-party payments on the profits of state-owned commercial banks.